THE EFFECTS OF HEALTH EDUCATION ON PREVENTING THE DANGERS OF PESTICIDE EXPOSURE ON FARMERS' KNOWLEDGE AND SKILLS IN USING PERSONAL PROTECTIVE EQUIPMENT (PPE) - Elisa Khoerul Wijayanti; Nurul Fatwati Fitriana (Universitas Kadiri, 2025)
Pesticides are chemical substances that eliminate pests, insects, weeds, and fungi. Improper use can lead to poisoning among farmers. The use of PPE during mixing and spraying can prevent the dangers of pesticide exposure. Objective : To determine the effects of health education on preventing the dangers of pesticide exposure on farmers' knowledge and skills in using PPE in Karanganyar Village. Method : This quantitative study used a pre-experimental design with a one- group pre-test and post-test approach. The respondents were 48 farmers, and the instruments used were questionnaires and observation sheets. Results : There is a significant effect on farmers' knowledge levels before and after being given health education intervention to prevent the dangers of pesticide exposure, with a p-value of 0.001 (p 0.05). There is also a significant effect on skill levels before and after being given PPE usage simulation, with a p-value of 0.001 (p 0.05). Conclusion : Health education significantly affects farmers' knowledge and skills in preventing the dangers of pesticide exposure by using PPE.